2018
DOI: 10.1097/qad.0000000000001706
|View full text |Cite
|
Sign up to set email alerts
|

The validity of self-reported antiretroviral use in persons living with HIV

Abstract: Self-reported ART use has high specificity and moderate sensitivity providing reasonable, but conservative estimates of population-based ART use. There is more under-reporting of ART use among younger persons and traders suggesting a need for more research on barriers to self-reporting of ART use in these sub-groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 16 publications
1
42
1
Order By: Relevance
“…We also used self-reported data to assess ART use, which may be subject to reporting bias. However, in a validation study we found a high specificity (99%) and moderate sensitivity (76%) of self-reported ART use compared to detection of antiretroviral drugs in plasma, regardless of migrant status 56 . Lastly, while our results may not be generalizable to hotspots outside of the Lake Victoria basin, they should motivate investigation into the epidemic and population dynamics that give rise to hotspots elsewhere and caution assumptions about them in the absence of data.…”
Section: Discussionmentioning
confidence: 65%
“…We also used self-reported data to assess ART use, which may be subject to reporting bias. However, in a validation study we found a high specificity (99%) and moderate sensitivity (76%) of self-reported ART use compared to detection of antiretroviral drugs in plasma, regardless of migrant status 56 . Lastly, while our results may not be generalizable to hotspots outside of the Lake Victoria basin, they should motivate investigation into the epidemic and population dynamics that give rise to hotspots elsewhere and caution assumptions about them in the absence of data.…”
Section: Discussionmentioning
confidence: 65%
“…Of note, a number of studies have reported denial of ART use among individuals determined to be taking therapy based on drug level testing. [35][36][37] Whether the mechanism of effect is due to poor adherence or virologic mechanisms, our nding that NNRTI resistance, present in 10-20% of individuals initiating DTG in the region, is associated with a reduction in e cacy of DTG-based ART is has multiple public health implications. First, ensuring adequate virologic monitoring occurs with DTG-based regimens will remain a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to disclose HIV status and ART use has been confirmed in at least two settings namely a multinational clinical trial reported by Fogel et al (5) and population studies in Kenya (6) and Uganda (7). This suggests that this phenomenon might be more widespread than previously thought and should be of concern in other blood donor populations or cohort studies of putative EC.…”
Section: Introductionmentioning
confidence: 87%